Combination of immune checkpoint blockade and targeted gene regulation of angiogenesis for facilitating antitumor immunotherapy - Zhan, Jing; Zhang, Manli; Zhou, Lili; He, Chuan (Frontiers in Bioengineering and Biotechnology, 2023)
The rapid development of tumor immunotherapy has improved the management of patients with cancer. However, several key problems of tumor immunotherapy, including the insufficient activation of effector T cells, poor tumor invasion, and poor immune killing ability, lead to a low response rate. In the present study, a synergistic strategy was developed by combining in situ tumor vaccines, gene-mediated downregulation of tumor angiogenesis, and anti-PD-L1 therapy. In situ tumor vaccines and antitumor angiogenesis were achieved by codelivering unmethylated cytosine-phosphate-guanine (CpG) and vascular endothelial growth factor (VEGF)-silencing gene (shVEGF) via a hyaluronic acid (HA)-modified HA/PEI/shVEGF/CpG system. Necrotic tumor cells and CpG adjuvants formed in situ tumor vaccines and activated the host immune response. Moreover, VEGF silencing reduced tumor angiogenesis and prompted the homogeneous distribution of tumor blood vessels to facilitate immune cell infiltration. Meanwhile, anti-angiogenesis also improved the immunosuppressive tumor microenvironment. To further improve the specific tumor-killing effect, an anti-PD-L1 antibody was introduced for immune checkpoint blockade, thereby boosting antitumor immune responses. The combination therapy strategy presented in the present study could act in the multiple stages of the tumor immunotherapy cycle, which is expected to offer a new avenue for clinical tumor immunotherapy.